Enzymatic Assays to Explore Viral mRNA Capping Machinery. (3rd August 2021) - Kasprzyk, Renata; Jemielity, Jacek
Abstract: In eukaryotes, mRNA is modified by the addition of the 7‐methylguanosine (m 7 G) 5′ cap to protect mRNA from premature degradation, thereby enhancing translation and enabling differentiation between self (endogenous) and non‐self RNAs (e. g., viral ones). Viruses often develop their own mRNA capping pathways to augment the expression of their proteins and escape host innate immune response. Insights into this capping system may provide new ideas for therapeutic interventions and facilitate drug discovery, e. g., against viruses that cause pandemic outbreaks, such as beta‐coronaviruses SARS‐CoV (2002), MARS‐CoV (2012), and the most recent SARS‐CoV‐2. Thus, proper methods for the screening of large compound libraries are required to identify lead structures that could serve as a basis for rational antiviral drug design. This review summarizes the methods that allow the monitoring of the activity and inhibition of enzymes involved in mRNA capping. Abstract : To escape recognition by the host innate immune system, viruses often incorporate 5′ caps into their mRNAs. The differences in mRNA capping make this process an interesting therapeutic target. Here, we review methods to explore the enzymes involved in cap biosynthesis. Such methods allow inhibitor selection, facilitating antiviral drug discovery, which is especially important considering the ongoing COVID‐19 pandemic and possible future outbreaks.